Pengukuran Tingkat Ketidaksesuaian Ketebalan Dinding Galon (Jugs) Melalui Pendekatan Statistical Process Control (SPC) - Daisykarenas Siwi; Anda Iviana Juniani; Wiediartini Wiediartini (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Quality is one of the important things that consumers consider in choosing the productthey will use. The high level mismatch of gallon wall thickness that occurred as of December 2017 tomeet the specifications reached 80,87% at point A0; 0,007% at point A1; 91,6% at point A2; 2,39%at point A3; 98,4% at point A4; 92,03% at point C0; 10,35% at point C1; 36,65% at point C2;30,67% at point C3; and 96,81% at point C4. So quality must be maintained as an effort to attract theattentionof consumers and consumer interest in using gallons from this plastic packaging industry. Toanalyze the quality of gallons used the SPC approach and process capability analysis. After analyzingthe process production of gallon through the SPC approach using the I-MR control chart there arestill many points out of control at any point observation that isA0, A1, A2, A3, A4, C0, C1, C2, C3,and C4. Process capability analysis also shows that there is a process that is said to be improper (Cp<1,00) must be repaired even though the process is perfect and unable to meet the specified thicknessspecifications (Cpk <1,00) indicates the accuracy of the process is less which means it needs to bedone improvement by find the root cause of the problem.